STUDI LABORATORIUM PENGARUH KECEPATAN ALIR FLUIDA DUA FASA MINYAK/AIR TERHADAP POLA ALIRAN FLUIDA PADA PIPA HORIZONTAL - Aslam, Fachry
In oil-production process, it is commonly happened that water from the formation is also produced. The existence of this water in the pipe will affect the oil flow to the processing unit, because when two immiscible fluids flow together in a pipe, these fluids will have different behavior compared to a single phase fluid. Depends on fluids velocity, water cut, and other properties, a flow regime (flow pattern) will be formed. In this case, the study focused on dispersed and stratified flow pattern. At the actual field, in higher level of water cut, a dispersed flow pattern is expected; because if water and oil are in a stratified flow pattern, the difference of viscosity - where water have smaller viscosity compared to oil - will caused water to flow better than the oil, thus slowing down the oil flow; even worse in an actual field where the pipes are not always in a fully horizontal position. This study observe the effect of the fluids velocity to the formed flow pattern; from a dispersed flow pattern to a stratified flow pattern. The density difference between these two fluids will caused the oil to rise and making a stratified flow pattern. In this study, observation is performed in fluids velocity of 0.007854 m/s to 1.5708 m/s. Theoretically, higher velocity of the fluids needs a longer time period to form a stratified flow pattern. In this study, the condition is varied to 70%, 80%, and 90% water cut. In the 70% and 80% water cut level, the minimum velocity needed for the two fluids to not become a stratified flow pattern are achieved in 0.7854 m/s and 1.5707 m/s. Meanwhile, in 90% water cut level, a stratified flow pattern is still formed even at the maximum fluid velocity test, thus a conclusion was made that it took more than 1.5707 m/s mixture velocity to avoid a stratified flow pattern in a 90% water cut condition.